Research on Mechanism of Enhancing Recovery of Heavy Oil With N2 Huff-n-Puff Assisted by Viscosity Reducer - Tao, Lei; Huang, Sen; Liu, Yali; Cheng, Hao; Du, Huajun; Wang, Cheng; Zhang, Na; Li, Jinlong (Frontiers in Energy Research, 2020)
In this paper, viscosity reducers with viscosity reduction ability and foaming ability and the recovery efficiency in N2 huff-n-puff were studied. The optimal 4# viscosity reducer was selected by evaluating the viscosity reduction ability, emulsion stability, interfacial performance, and foaming. The huff-n-puff experiments of single sandpack and dual sandpack were carried out under the reservoir conditions. The results showed that the viscosity reduction rate of 4# viscosity reducer was more than 90% at 50–90°C, and it could form a stable oil/water emulsion when applied to heavy oil. Under the action of 4# viscosity reducer, the interfacial tension between oil and water decreased to 0.41 and 0.19 IFT/mN·m−1 at 50 and 80°C, respectively. In the single sandpack huff-n-puff experiment, the 4# viscosity reducer could inhibit N2 bubbles coalesced in large channels and improve the mobility of heavy oil. Compared with N2 huff-n-puff, the recovery rate of N2 huff-n-puff assisted by 4# increased by 8.53%. In the dual sandpack huff-n-puff experiment, the N2 was inhibited to flow from the low permeability sandpack to the high permeability sandpack by 4# viscosity reducer, and the gas production of the low permeability sandpack increased by 284.71%. Under the combined action of viscosification and plugging, the total oil production of the sandpack increased by 7.88%. Therefore, N2 huff-n-puff assisted by viscosity reducer has a significant effect on enhancing oil recovery in heavy oil reservoirs.